2021
DOI: 10.3389/fmed.2021.649263
|View full text |Cite
|
Sign up to set email alerts
|

Microcirculatory Response to Changes in Venoarterial Extracorporeal Membrane Oxygenation Pump Flow: A Prospective Observational Study

Abstract: Background: Venoarterial extracorporeal membrane oxygenation (VA-ECMO) pump flow is crucial for maintaining organ perfusion in patients with cardiogenic shock, but VA-ECMO pump flow optimization remains as a clinical challenge. This study aimed to investigate the response of sublingual microcirculation to changes in VA-ECMO pump flow.Methods: Sublingual microcirculation was measured before and after changing VA-ECMO pump flow according to the treatment plan of ECMO team within 24 h and at 24-48 h after VA-ECMO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
(39 reference statements)
1
2
0
Order By: Relevance
“…Moreover, microcirculatory flow response as a result of 50% pump flow decrease from the baseline visualized by hand-held vital microscopy occurring during VA-ECMO reliably predicted success of weaning [ 69 ]. These results were confirmed in a study by Wei et al, however, in addition they also identified that some patients paradoxically showed a reduction in microcirculatory flow after an increase in VA-ECMO pump flow [ 70 ]. Similarly, successful improvement of perfused small vessel density within the first 24 h of VA-ECMO initiation was able to accurately predict in-ICU mortality [ 71 ].…”
Section: Introductionsupporting
confidence: 58%
“…Moreover, microcirculatory flow response as a result of 50% pump flow decrease from the baseline visualized by hand-held vital microscopy occurring during VA-ECMO reliably predicted success of weaning [ 69 ]. These results were confirmed in a study by Wei et al, however, in addition they also identified that some patients paradoxically showed a reduction in microcirculatory flow after an increase in VA-ECMO pump flow [ 70 ]. Similarly, successful improvement of perfused small vessel density within the first 24 h of VA-ECMO initiation was able to accurately predict in-ICU mortality [ 71 ].…”
Section: Introductionsupporting
confidence: 58%
“…On the other hand, crystalloid resuscitation is the norm during ECMO to sustain adequate flows. The benefit of temporarily improved flows is then counter-balanced with fluid overload that potentially worsens EG injury and microcirculation [213] . Finally, corticosteroids are often used in the management of critically ill children requiring CPB or ECMO to attenuate the pro-inflammatory response, treat absolute or relative adrenal insufficiency, and promote convalescence [214] , [215] .…”
Section: Extracorporeal Life Supportmentioning
confidence: 99%
“…Whilst much of VA ECMO monitoring centres around adequacy of macrocirculatory hemodynamics, oxygen delivery to tissues is dependent on maintaining adequate microcirculatory flow. There has been increasing interest in more directly monitoring tissue perfusion (most commonly through the sublingual microcirculation) to evaluate prognosis, but this is still mainly experimental and has not been routinely incorporated into clinical practice [15][16][17].…”
Section: Key Pointsmentioning
confidence: 99%